(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Recent earthquakes with low to moderate magnitude very close to Dhaka are certainly indications of its earthquake source and vulnerability. The study was conducted to bring out the present earthquake vulnerability status of 10 wards, out of 91 wards, in Dhaka and to assume the probable loss of lives and property by studying the previous records in the city and getting respondents opinion about it. The ward no. 15 show higher building density with older age of building i.e. more than 30 years of age, and present more unreinforced buildings than other wards which might be the cause of increased vulnerability to earthquake. Among the 10 wards, the ward no. 13 and 17 are more vulnerable to earthquake due to highest soft storey buildings, heavy overhang, presence of short columns and poor physical condition of buildings. The result of the survey found that more than half (64%) of the respondents considered Dhaka city as the highly vulnerable to earthquake because of most of the infrastructures were built without maintaining the building code and also without keeping proper spaces among them. Besides these, 40% respondents stated that the impact would be obvious on life as there would not be enough time to escape people from the high rise buildings to safer places during the earthquake. Almost all the respondents (86%) consider that the southern part of Dhaka city is more vulnerable than other parts of the city due to the increasing urbanization and poorly structured old buildings. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22049 J. Environ. Sci. & Natural Resources, 6(1): 107-112 2013